A SIFT-MS study of positive and negative ion chemistry of the ortho-, meta- and para-isomers of cymene, cresol, and ethylphenol - Swift, Stefan J; Sixtová, Nikola; Omezzine Gnioua, Maroua; Španěl, Patrik (Physical chemistry chemical physics, 2023)
Selected Ion Flow Tube Mass Spectrometry (SIFT-MS) is a soft ionisation technique based on gas phase ion-molecule reaction kinetics for the quantification of trace amounts of volatile organic compound vapours. One of its previous limitations is difficulty in resolving isomers, although this can now be overcome using different reactivities of several available reagent cations and anions (H3O+, NO+, O2+˙, O-˙, OH-, O2-˙, NO2-, NO3-). Thus, the ion-molecule reactions of these eight ions with all isomers of the aromatic compounds cymene, cresol and ethylphenol were studied to explore the possibility of their immediate identification and quantification without chromatographic separation. Rate coefficients and product ion branching ratios determined experimentally for the 72 reactions are reported. DFT calculations of their energetics confirmed the feasibility of the suggested reaction pathways. All positive ion reactions proceeded fast but largely did not discriminate between the isomers. The reactivity of the anions was much more varied. In all cases, OH- reacts by proton transfer forming (M-H); NO2- and NO3- were unreactive. The differences observed for product ion branching ratios can be used to identify isomers approximately.